The Effectiveness of Ethanol Extract of Robusta Coffee Seeds on Blood Glucose, Urea, and Creatinine Levels of Male White Rats Induced by Streptozotocin: Efektivitas Ekstrak Etanol Biji Kopi Robusta terhadap Kadar Glukosa Darah, Urea, dan Kreatinin Tikus Putih Jantan yang Diinduksi Streptozotocin - Tandi, Joni; Marsella, Mimi; Suarsana, I Made Agus; Dewi, Niluh Puspita; Magfirah, Magfirah; Handayani, Tien Wahyu; Kanan, Maria (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Traditional medicine plays a role in alternative treatment systems for diabetes mellitus. Objectives: This study aimed to screen the secondary metabolite of the ethanol extract from robusta coffee (Coffea canephora Pierre) seeds. We aimed to clarify the effects of these extracts on blood glucose, urea, and creatinine levels in Streptozotocin-Induced Diabetic Rats. Material and Methods: Phytochemical screening of extracts was carried out qualitatively according to standard methods. The rats were administered ethanol extracts of C. canephora Pierre seeds at doses of 100, 200, and 300 mg/kg body weight for 28 days. Blood glucose, urea, and creatinine levels were then compared between the control and diabetes groups. Results: The ethanol extract of C. canephora Pierre seeds contains alkaloids, flavonoids, saponins, and tannins. Group doses of 100-300 mg/kg body weight can significantly reduce blood glucose, urea, and creatinine levels. It can be concluded that the ethanol extract C. canephora Pierre seeds is a potential source of antidiabetic. Conclusions: The ethanol extract of C. canephora Pierre seeds shows potential as an antidiabetic agent.